The Role of Whistleblowing Systems and Ethical Culture as Moderation in The Prevention of Financial Reporting Fraud - Willyanto Kartiko Kusumo; Nanang Ari Utomo; Purwati Purwati (Lembaga Riset dan Inovasi Al-Matani, 2026)
The purpose of this study was to analyze the consistency of factors that affect the intention of behavior based on The Theory of Planned Behavior with whistleblowing and ethical culture as a variable of moderation in fraud prevention. The sampling method used is purposive sampling. Respondents consisted of 109 finance/accounting managers from 27 state-owned companies in Semarang. Data analysis was done by structural equation modeling (SEM) based on Partial Least Squares (PLS) with SmartPLS 4.0. The novelty of this study, is first, the addition of whistleblowing and ethical culture as moderation variables, which can affect the intention of behavior in fraud prevention. Second, there is an additional one new independent variable, namely moral commitment, can be a driving factor that adds to the accuracy of predictions of one's behavioral intentions. The results showed that behavioral attitudes, subjective norms, behavioral control and moral commitment have a positive and significant effect on the intention of fraud prevention behavior where the value of t count is greater than T table (>1.64) and p-value is smaller than alpha 5% (0.000 < 0.05). As for the moderation variable, the findings suggest that ethical culture can strengthen the influence of behavioral intentions on fraud prevention. However, whistleblowing does not contribute significantly because employees still have difficulty understandingreporting procedures. Therefore, companies need to strengthen whistleblowing systems with collaboration between departments supported by top management, such as regular internal audits, strict anti-fraud policies, building a culture of transparency and integrity and providing secure reporting channels to improve internal controls, as part of fraud prevention. This research provides an academic contribution in understanding the relationship between various factors that drive behavior in fraud prevention efforts in realizing transparent, accountable and integrity financial governance.